Photovoltaic packaging adhesive film, preparation method thereof and photovoltaic module
By using materials such as modified antacids and ion adsorbents in photovoltaic modules, the problem of accelerated Na+ ion migration in photovoltaic modules is solved, and the stability and performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202510199344.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-24
AI Technical Summary
Photovoltaic modules are prone to PID in humid and hot environments, resulting in accelerated Na+ ion migration and affecting the long-term stability and performance of the battery cells.
A photovoltaic encapsulation film including a water-blocking layer adhesive film, a water-absorbing layer adhesive film and an EVA adhesive film are used. Modified antacids are added to the water-blocking layer adhesive film, and the water-absorbing layer adhesive film contains ionic adsorbents and hydrophilic additives. The acid-resistant and water-resistant properties of the adhesive film are improved through laminated structure and modification treatment.
Effectively adsorb Na+ ions, reduce the impact of water vapor on the battery cell, and improve the long-term stability and photoelectric conversion efficiency of the battery cell.
Smart Images

Figure CN119684913A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of packaging materials for photovoltaic modules, and in particular to a photovoltaic packaging film and a preparation method thereof, and a photovoltaic module. Background Art
[0002] Photovoltaic modules are the main equipment for solar photovoltaic power generation. When sunlight shines on photovoltaic modules, current will be generated and output through related equipment. The structure includes tempered glass panel, EVA (ethylene-vinyl acetate copolymer) film, crystalline silicon cell, EVA film and backplane (TPT board). With the continuous development of photovoltaic module technology and some problems found in use, there is a risk of potential induced degradation (PID) of photovoltaic modules under negative bias, that is, the current leakage caused by voltage difference in photovoltaic modules in a humid environment will cause the performance of the modules to decline.
[0003] The PID phenomenon of photovoltaic modules is affected by the Na + Ions migrate to the cell to damage the anti-reflection layer / passivation layer, and when in an acidic or water-rich environment, it will accelerate the Na + On the other hand, it is subject to the corrosion of battery slurry by free acetic acid produced by hydrolysis of EVA film. Generally, ion capture agents are added to improve Na + The problem of ion migration; adding modified antacids to neutralize acetic acid and reduce the corrosion of acidic media to the slurry.
[0004] However, the adsorption effect of ion capture agents is closely related to their dispersion, concentration and water vapor. When the battery is placed in a hot and humid environment, the Na + The migration speed of ions makes it difficult for ion capture agents to fully achieve the effect of adsorbing ions. In addition, inorganic antacids also have dispersion problems in EVA films and are prone to agglomeration, resulting in poor anti-acid effects, which in turn affects the long-term stability of the battery cell.
[0005] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the invention
[0006] The embodiments of the present application provide a photovoltaic encapsulation film and a preparation method thereof and a photovoltaic module to solve or alleviate one or more of the technical problems raised above.
[0007] In a first aspect, an embodiment of the present application provides a photovoltaic encapsulation film, comprising a water-blocking layer film, a water-absorbing layer film and an EVA layer film stacked in sequence; The water-blocking layer film comprises the following raw materials in parts by weight: 90-100 parts of EVA resin, 0.4-0.8 parts of cross-linking agent, 0.6-1.0 parts of first auxiliary cross-linking agent, 0.1-0.5 parts of coupling agent, 0.01-0.15 parts of light stabilizer and 0.1-0.3 parts of modified antacid; The water-absorbing layer film comprises the following raw materials in parts by weight: 5-20 parts of ion adsorbent, 25-50 parts of hydrophilic additive, and 30-40 parts of second auxiliary cross-linking agent; The EVA layer film comprises the following raw materials in parts by weight: 90-100 parts of EVA resin, 0.4-0.8 parts of cross-linking agent, 0.6-1.0 parts of first auxiliary cross-linking agent, 0.1-0.5 parts of coupling agent and 0.01-0.15 parts of light stabilizer.
[0008] Optionally, the hydrophilic auxiliary agent includes one of a hydrophilic monomer and a hydrophilic polymer.
[0009] Optionally, the hydrophilic monomer includes one or more of hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone NVP, dimethylaminoethyl methacrylate, and polyvinyl pyrrolidone.
[0010] Optionally, the hydrophilic auxiliary agent includes a hydrophilic polymer obtained by polymerizing one or more of hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone NVP, dimethylaminoethyl methacrylate, and polyvinyl pyrrolidone; The number average molecular weight of the hydrophilic polymer is 2000-10000.
[0011] Optionally, the carbodiimide coupling agent is obtained from an isocyanate coupling agent under the catalytic action of an organic phosphorus catalyst.
[0012] Optionally, the ion adsorbent includes one or both of silicon dioxide and zirconium phosphate.
[0013] Optionally, the modified antacid includes one or both of modified magnesium hydroxide or modified magnesium oxide; Wherein, the modified magnesium hydroxide is magnesium hydroxide modified by a carbodiimide coupling agent; and the modified magnesium oxide is magnesium oxide modified by a carbodiimide coupling agent.
[0014] Optionally, the cross-linking agent includes one or both of tert-butyl peroxy-2-ethylhexanoate (TAEC) and tert-butyl peroxy-2-ethylhexyl carbonate (TBEC).
[0015] Optionally, the first auxiliary cross-linking agent includes one or more of TAIC, tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate and pentaerythritol tetraacrylate.
[0016] Optionally, the coupling agent includes one or more of 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane.
[0017] Optionally, the second auxiliary cross-linking agent includes one or more of ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate, tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate and pentaerythritol tetraacrylate.
[0018] Optionally, the thickness ratio of the water-blocking layer film, the water-absorbing layer film and the EVA layer film is (10-15): (1-2): (30-35).
[0019] In a second aspect, the present application provides a method for preparing a photovoltaic encapsulation film, comprising the following steps: According to the weight percentage, 90-100 parts of EVA resin are added to the mixing tank, and then 0.4-0.8 parts of the cross-linking agent, 0.6-1.0 parts of the first auxiliary cross-linking agent, 0.1-0.5 parts of the coupling agent, and 0.01-0.15 parts of the light stabilizer are mixed and added to the mixing tank, and then heated and heat-insulated, and then 0.1-0.3 parts of the modified antacid are added, and the mixture is allowed to stand and then extruded to obtain a water-blocking layer film; According to the weight ratio, 25-50 parts of the hydrophilic auxiliary agent and 30-40 parts of the second auxiliary cross-linking agent are mixed evenly to obtain a mixed solution, and then 5-20 parts of the ion adsorbent are added to the mixed solution and stirred, and the viscosity is adjusted to obtain a pre-water-absorbing layer film, and then the pre-water-absorbing layer film is roll-coated on the surface of the water-blocking layer film, and after curing treatment, a water-absorbing layer film is obtained; According to the weight percentage, 90-100 parts of EVA resin are added to a mixing tank, and then 0.4-0.8 parts of a cross-linking agent, 0.6-1.0 parts of a first auxiliary cross-linking agent, 0.1-0.5 parts of a coupling agent, and 0.01-0.15 parts of a light stabilizer are mixed and evenly added to the mixing tank, and then heated and heat-insulated and then extruded to obtain an EVA layer film; The EVA layer film is placed on the surface of the water-absorbing layer film, and the photovoltaic encapsulation film is obtained by compounding with an embossing roller.
[0020] Optionally, the curing treatment includes one of EB irradiation, UV curing or thermal curing.
[0021] In a third aspect, an embodiment of the present application provides a photovoltaic module, the photovoltaic module comprising: Battery cells; The photovoltaic encapsulation film as described above, or the photovoltaic encapsulation film prepared by the method as described above; The photovoltaic encapsulation film is used to encapsulate the solar cell.
[0022] The above technical solution adopted in the embodiment of the present application may have the following advantages: When Na + During ion migration, the ion adsorbent in the water-absorbing layer film can adsorb Na + ions, improving the anti-PID effect, while the hydrophilic additive can highly absorb water, reducing the impact of water vapor on the battery cell, and also provides an environment for the ion adsorbent to adsorb ions, effectively reducing the performance degradation of the battery cell; in addition, the modified antacid in the water-blocking layer film has a good dispersion effect in the EVA resin and is not easy to agglomerate, thereby improving the anti-acid effect; the water-absorbing layer film and the water-blocking layer film work together to effectively maintain the long-term stability and photoelectric conversion efficiency of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the multiple drawings represent the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings only depict some embodiments disclosed in the present application and should not be regarded as limiting the scope of the present application.
[0024] Figure 1 It is a schematic diagram of the structure of the photovoltaic encapsulation film provided in the embodiment of the present application.
[0025] Figure 2 It is a schematic diagram of the sea-island structure of the water-absorbing layer film provided in an embodiment of the present application.
[0026] Figure 3 This is the corrosion-resistant EL image of the photovoltaic encapsulation film provided in Example 1 of the present application.
[0027] Figure 4 This is the corrosion-resistant EL image of the photovoltaic encapsulation film provided in Comparative Example 1 of the present application.
[0028] Figure 5 This is an EL diagram of the PID test of the photovoltaic encapsulation film provided in Example 1 of the present application.
[0029] Figure 6 This is an EL diagram of the PID test of the photovoltaic encapsulation film provided in Example 2 of the present application.
[0030] Figure 7 This is an EL diagram of the PID test of the photovoltaic encapsulation film provided in Example 3 of the present application.
[0031] Figure 8 This is an EL diagram of the PID test of the photovoltaic encapsulation film provided in Example 4 of the present application.
[0032] Fig. 9 This is an EL diagram of the PID test of the photovoltaic encapsulation film provided in Example 5 of the present application.
[0033] Fig.10 This is the EL diagram of the PID test of the photovoltaic encapsulation film provided in Example 6 of the present application.
[0034] Fig.11 This is the EL diagram of the PID test of the photovoltaic encapsulation film provided in Example 7 of the present application.
[0035] Fig.12 This is an EL diagram of the PID test of the photovoltaic encapsulation film provided in Comparative Example 1 of the present application.
[0036] Fig.13 This is the EL diagram of the PID test of the photovoltaic encapsulation film provided in Comparative Example 2 of the present application.
[0037] Fig.14 This is the EL diagram of the PID test of the photovoltaic encapsulation film provided in Comparative Example 3 of the present application.
[0038] Fig.15 This is the EL diagram of the PID test of the photovoltaic encapsulation film provided in Comparative Example 4 of the present application.
[0039] Description of reference numerals: 1. Water-blocking layer film; 2. Water-absorbing layer film; 3. EVA layer film; 4. Ion adsorbent; 5. Hydrophilic additive. DETAILED DESCRIPTION
[0040] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. In the accompanying drawings, for clarity, the sizes of layers, regions, elements and their relative sizes may be exaggerated. Wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limitations on the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other.
[0041] It should be understood that when an element or layer is referred to as "on ...", "adjacent to ...", "connected to" or "coupled to" other elements or layers, it can be directly on, adjacent to, connected to or coupled to other elements or layers, or there can be intervening elements or layers. On the contrary, when an element is referred to as "directly on ...", "directly adjacent to ...", "directly connected to" or "directly coupled to" other elements or layers, there is no intervening element or layer. It should be understood that although the terms first, second, third, etc. can be used to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings of the present disclosure, the first element, component, region, layer or part discussed below can be represented as the second element, component, region, layer or part. And when the second element, component, region, layer or part is discussed, it does not indicate that the present application discloses the existence of the first element, component, region, layer or part.
[0042] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0043] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0044] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.
[0045] The following provides an explanation of the terms used in this application.
[0046] TAEC: tert-butyl peroxycarbonate-2-ethylhexanoate; TBEC: tert-butyl peroxy-2-ethylhexyl carbonate; GPTA: glyceryl triacrylate propoxylate; TAIC: triallyl isocyanurate; Light stabilizer 770: bis-2,2,6,6-tetramethylpiperidinol sebacate; Light stabilizer 292: bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate; EB: electron beam irradiation.
[0047] Hereinafter, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings. It should be noted that these exemplary embodiments can be implemented in many different forms and should not be construed as being limited to the embodiments described herein.
[0048] The embodiment of the present application provides a photovoltaic encapsulation film. The photovoltaic encapsulation film may include a water-blocking layer film, a water-absorbing layer film and an EVA layer film stacked in sequence; the water-blocking layer film includes the following raw materials in parts by weight: 90-100 parts of EVA resin, 0.4-0.8 parts of a cross-linking agent, 0.6-1.0 parts of a first auxiliary cross-linking agent, 0.1-0.5 parts of a coupling agent, 0.01-0.15 parts of a light stabilizer and 0.1-0.3 parts of a modified antacid; the water-absorbing layer film includes the following raw materials in parts by weight: 5-20 parts of an ion adsorbent, 25-50 parts of a hydrophilic auxiliary agent and 30-40 parts of a second auxiliary cross-linking agent; the EVA layer film includes the following raw materials in parts by weight: 90-100 parts of EVA resin, 0.4-0.8 parts of a cross-linking agent, 0.6-1.0 parts of a first auxiliary cross-linking agent, 0.1-0.5 parts of a coupling agent and 0.01-0.15 parts of a light stabilizer.
[0049] In the embodiments of the present application, Figure 2 As shown, the water-absorbing layer film forms an island structure, wherein the island component in the water-absorbing layer film is an ion adsorbent 4, and the sea component is a hydrophilic additive 5. The water-blocking layer film is in contact with the battery cell, while the EVA layer film is in contact with the glass. + When ions migrate to the battery cell under the action of the electric field, the island component is an ion adsorbent that can adsorb Na + ions, improving the anti-PID effect, while the sea component is a hydrophilic additive that can highly absorb water, reducing the impact of water vapor on the battery cell, and also provides an environment for the ion adsorbent to adsorb ions, effectively reducing the performance degradation of the battery cell; in addition, the modified antacid in the water-blocking layer film can improve its dispersion effect in the EVA film, reduce agglomeration, and thus improve the acid-resistant effect; the water-absorbing layer film and the water-blocking layer film work together to effectively maintain the long-term stability and efficiency of the battery cell.
[0050] It should be noted that Na + Ions generally come from glass and EVA film, especially in hot and humid environments. + Ions will migrate into the cell through the electric field, thereby damaging the anti-reflection layer and the passivation layer, reducing the efficiency and stability of the cell. In the embodiment of the present application, the water-absorbing layer film is between the EVA layer film and the water-blocking layer film, which can effectively absorb water to provide the ion adsorbent with Na + ion environment, reducing Na + The impact of ions on the battery cells also blocks the impact of water vapor on the battery cells.
[0051] In some embodiments, the light stabilizer includes one or both of light stabilizer 292 and light stabilizer 770 .
[0052] In the embodiments of the present application, the light stabilizer can reduce the damage of ultraviolet rays to the EVA resin by absorbing ultraviolet rays, and can also inhibit the generation of free radicals, thereby reducing the oxidation and degradation rate of the EVA resin; in addition, it also improves the weather resistance of the resin, maintains the mechanical properties and appearance of the resin, and reduces the yellowing and brittleness phenomena.
[0053] In an optional embodiment, the hydrophilic auxiliary agent includes one of a hydrophilic monomer and a hydrophilic polymer.
[0054] In the embodiment of the present application, one of the hydrophilic monomer and the hydrophilic polymer is used as a hydrophilic auxiliary agent in the water-absorbing layer film to absorb water vapor to block the influence of water vapor on the battery cell, and at the same time, it absorbs water vapor to provide the ion adsorbent with Na + ionic environment; and a mixture of hydrophilic monomers and hydrophilic polymers is selected as the hydrophilic additive. The two can work synergistically with each other to enhance the water adsorption effect, so that the film maintains better performance in a humid environment.
[0055] In an optional embodiment, the hydrophilic monomer includes one or more of hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone NVP, dimethylaminoethyl methacrylate, and polyvinyl pyrrolidone.
[0056] In the embodiments of the present application, the hydrophilic monomers mentioned above can interact with water molecules in the water-absorbing layer film through hydrogen bonds to form a hydration layer, absorb moisture, and thus effectively block the influence of water vapor on the battery cell.
[0057] In an optional embodiment, the hydrophilic additive includes a hydrophilic polymer obtained by polymerizing one or two of hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone NVP, dimethylaminoethyl methacrylate, and polyvinyl pyrrolidone; and the number average molecular weight of the hydrophilic polymer is 2000-10000.
[0058] In the embodiment of the present application, when the number average molecular weight is lower than 2000, the hydrophilic polymer will be too short to form a stable three-dimensional network; when the number average molecular weight is higher than 10000, the hydrophilic polymer will have poor fluidity, which will limit the entry of water. Therefore, the hydrophilic polymer with a number average molecular weight in the range of 2000 to 10000 allows the hydrophilic polymer to form a three-dimensional network structure when absorbing water, better capture and retain water, form a hydration layer, and block the influence of water vapor on the battery cell. In addition, the hydrophilic polymer interacts with water molecules to form a larger hydrophilic surface area, further improving the overall water absorption performance.
[0059] In an optional embodiment, the ion adsorbent includes one or both of silicon dioxide and zirconium phosphate. Further, the particle size of the silicon dioxide is 10 nm to 10 μm.
[0060] In the embodiment of the present application, the surface of the silicon dioxide contains hydroxyl groups, which can be adsorbed with sodium ions through electrostatic attraction; and the silicon dioxide is porous, providing a large specific surface area, so that sodium ions can effectively enter and be captured. The structure of zirconium phosphate contains phosphate (PO4³⁻), which can be combined with sodium ions through ion exchange; zirconium phosphate also has good complexing ability, and can form a stable complex with sodium ions to enhance its capture effect. Furthermore, the particle size of silicon dioxide is 10nm~10μm, and the particle size of silicon dioxide is small, which can provide a larger specific surface area, increase the contact opportunity with sodium ions, and help improve the adsorption efficiency. In addition, silicon dioxide with a smaller particle size has a richer pore structure, which allows sodium ions to enter its interior more easily and enhance the capture ability. When the particle size of silicon dioxide is greater than 10μm, the fluidity of silicon dioxide is poor and it is difficult to disperse evenly, thereby reducing the capture efficiency of sodium ions.
[0061] In an optional embodiment, the modified antacid includes one or both of modified magnesium hydroxide or modified magnesium oxide; wherein the modified magnesium hydroxide is magnesium hydroxide modified by a carbodiimide coupling agent; and the modified magnesium oxide is magnesium oxide modified by a carbodiimide coupling agent. Further, the particle size of the magnesium dioxide is 50nm~5μm, and the coverage rate of the modified magnesium dioxide is 5~20%.
[0062] In the embodiment of the present application, the surface of magnesium hydroxide or magnesium oxide is modified by a carbodiimide coupling agent, which can reduce the agglomeration of magnesium hydroxide or magnesium oxide and improve its dispersion performance, while also reducing the amount of magnesium hydroxide or magnesium oxide used and reducing the effect of magnesium hydroxide or magnesium oxide on the light transmittance of the film. The carbodiimide coupling agent has a highly unsaturated structure, which can react with moisture immersed in a hot and humid environment to form urea, reducing water vapor transmission, and can also easily react with carboxylic acid generated by EVA hydrolysis to form stable urea, thereby improving the hydrolysis stability of the EVA resin and maintaining the long-term stability of the battery cell in a hot and humid environment.
[0063] In an optional embodiment, the carbodiimide coupling agent is obtained by an isocyanate coupling agent under the catalysis of an organic phosphorus catalyst, and the isocyanate coupling agent includes 3-isocyanate propyl triethoxysilane and 3-isocyanate propyl trimethoxysilane. The ratio of the amount of the reactants of 3-isocyanate propyl triethoxysilane and 3-isocyanate propyl trimethoxysilane is 1:1, and the carbodiimide coupling agent is obtained by catalysis of an organic phosphorus catalyst under a temperature of 100°C. The ratio of the amount of the reactants of 3-isocyanate propyl triethoxysilane and 3-isocyanate propyl trimethoxysilane is 1:1, which can balance the reaction rates of the two isocyanate groups while maintaining the stability of the two during the reaction process, so that the preparation of the carbodiimide coupling agent has a higher conversion efficiency. Isocyanate coupling agent is used as raw material, and isocyanate coupling agent is both a coupling agent and a water barrier agent. On the one hand, it can play the role of a coupling agent to treat the surface of magnesium hydroxide or magnesium oxide, and on the other hand, it can react with acid and water to reduce water vapor transmission.
[0064] In an optional embodiment, the cross-linking agent includes one or both of tert-butyl peroxy-2-ethylhexanoate (TAEC) and tert-butyl peroxy-2-ethylhexyl carbonate (TBEC).
[0065] In the embodiments of the present application, the cross-linking agent can enhance the heat resistance of the film, making it less likely to deform or degrade in a high temperature environment, thereby improving its thermal stability; the cross-linking agent can form a network structure between the polymers through cross-linking, thereby enhancing the strength and toughness of the film, and improving its tear and compression resistance. The cross-linking agent can also improve the corrosion resistance of the water-blocking layer film and the EVA layer film. In addition, the cross-linking agent can improve the physical properties of the water-blocking layer film and the EVA layer film, such as improving transparency, reducing gas permeability, etc., thereby improving its performance in photovoltaic module packaging.
[0066] In an optional embodiment, the first auxiliary cross-linking agent includes one or more of TAIC, tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate and pentaerythritol tetraacrylate.
[0067] In the embodiment of the present application, the first co-crosslinking agent is added to the water-blocking layer film, which can improve the crosslinking degree of the water-blocking layer film, improve the overall strength and durability of the water-blocking layer, and also improve the water resistance, thermal stability, corrosion resistance and mechanical properties of the water-blocking layer film.
[0068] In an optional embodiment, the coupling agent includes one or more of 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane.
[0069] In the embodiments of the present application, the coupling agent can improve the compatibility between the EVA resin and other additives, and can improve the water penetration resistance of the EVA film, and reduce the influence of moisture on the film performance. In addition, the coupling agent added to the water-blocking layer film and the EVA layer film can also form a covalent bond with the EVA matrix, enhance the adhesion between the film and the substrate (such as glass, metal, etc.), and improve the interface bonding strength.
[0070] In an optional embodiment, the second auxiliary cross-linking agent includes one or more of ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate, tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate and pentaerythritol tetraacrylate.
[0071] In the embodiment of the present application, the second co-crosslinking agent forms a more stable three-dimensional network structure by chemically crosslinking with the hydrophilic auxiliary agent, effectively improving the hydrolysis resistance and anti-aging performance of the water-absorbing layer film, and extending the service life of the photovoltaic module. The second co-crosslinking agent increases the crosslinking density of the water-absorbing layer film, thereby enhancing the mechanical properties and stability of the water-absorbing layer film, ensuring that the water-absorbing layer film will not be excessively expanded or degraded due to water vapor or environmental stress during use. In addition, the second co-crosslinking agent can also improve the thermal stability and heat resistance of the water-absorbing layer film, ensuring that the photovoltaic encapsulation film can still effectively block water vapor and maintain structural integrity under high temperature conditions, and provide an environment for ion adsorption, thereby improving the protective performance of the entire photovoltaic encapsulation film.
[0072] In an optional embodiment, the thickness ratio of the water-blocking film, the water-absorbing film and the EVA film is (10-15): (1-2): (30-35). For example, the thickness ratio of the water-blocking film, the water-absorbing film and the EVA film is 10:1:30 and 15:2:35.
[0073] The present application embodiment may also provide a method for preparing a photovoltaic encapsulation film. The preparation method comprises the following steps: According to the weight percentage, 90-100 parts of EVA resin are added to the mixing tank, and then 0.4-0.8 parts of the cross-linking agent, 0.6-1.0 parts of the first auxiliary cross-linking agent, 0.1-0.5 parts of the coupling agent, and 0.01-0.15 parts of the light stabilizer are mixed and added to the mixing tank, and then heated and heat-insulated, and then 0.1-0.3 parts of the modified antacid are added, and the mixture is allowed to stand and then extruded to obtain a water-blocking layer film; According to the weight ratio, 25-50 parts of the hydrophilic auxiliary agent and 30-40 parts of the second auxiliary cross-linking agent are mixed evenly to obtain a mixed solution, and then 5-20 parts of the ion adsorbent are added to the mixed solution and stirred, and the viscosity is adjusted to obtain a pre-water-absorbing layer film, and then the pre-water-absorbing layer film is roll-coated on the surface of the water-blocking layer film, and after curing treatment, a water-absorbing layer film is obtained; According to the weight percentage, 90-100 parts of EVA resin are added to a mixing tank, and then 0.4-0.8 parts of a cross-linking agent, 0.6-1.0 parts of a first auxiliary cross-linking agent, 0.1-0.5 parts of a coupling agent, and 0.01-0.15 parts of a light stabilizer are mixed and evenly added to the mixing tank, and the mixture is heated and heat-insulated, left to stand, and then extruded to obtain an EVA layer film; The EVA layer film is placed on the surface of the water-absorbing layer film, and the photovoltaic encapsulation film is obtained by compounding with an embossing roller.
[0074] In an optional embodiment, the curing process includes one of EB irradiation, UV curing or thermal curing.
[0075] In the embodiment of the present application, after the pre-water-absorbing layer film is treated by the above-mentioned curing method, it can further attract Na+ ions to reduce the migration rate and provide an adsorption environment for the ion adsorbent. In addition, during the preparation process of the water-absorbing layer film, the ion adsorbent is added to the hydrophilic additive, and the hydrophilic additive can fully wet and disperse the ion adsorbent, thereby improving the problem of uneven dispersion of the ion adsorbent and thus improving the ion adsorbent's absorption of Na+. + Ion adsorption effect.
[0076] The following specific examples further illustrate the present application, but should not be construed as limiting the present application. Without departing from the spirit and substance of the present application, modifications or replacements made to the methods, steps or conditions of the present application are within the scope of the present application.
[0077] [Example 1] like Figure 1 As shown, a specific structure of a photovoltaic encapsulation film includes a water-blocking layer film 1, a water-absorbing layer film 2 and an EVA layer film 3 stacked in sequence, wherein the water-blocking layer film 1 contacts the battery cell, and the EVA layer film 3 contacts the glass.
[0078] A specific preparation process of a photovoltaic encapsulation film includes the following steps: S1: According to the weight percentage, 98 parts of EVA resin are added to the mixing tank, and then 0.6 parts of cross-linking agent tert-butyl peroxycarbonate-2-ethylhexanoate TAEC, 0.4 parts of the first auxiliary cross-linking agent TAIC, 0.4 parts of the first auxiliary cross-linking agent ethoxylated trimethylolpropane triacrylate, 0.3 parts of coupling agent 3-methacryloxypropyl triethoxysilane and 0.1 parts of light stabilizer 770 are mixed evenly to form a liquid auxiliary agent, and then the liquid auxiliary agent is sprayed on the EVA resin particles, and then a heating jacket is heated at a temperature of 50°C for 2 hours before being added. After mixing 0.2 parts of modified antacid for 2 hours, the outlet module temperature was set to 75°C and the film outlet temperature was set to 95°C for casting and extrusion to obtain a water-blocking layer film; wherein, the modified antacid is modified magnesium dioxide, and the modified magnesium dioxide is magnesium dioxide coated with a carbodiimide coupling agent (the particle size of magnesium dioxide is 0.5 μm, the coating rate is 5%, and the granulation concentration is 5%); the carbodiimide coupling agent is prepared by an isocyanate coupling agent (3-isocyanatepropyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane) at a temperature of 100°C under the catalysis of an organic phosphorus catalyst.
[0079] S2: According to the weight ratio, 20 parts of ion adsorbent silica (particle size of 50nm) are added to 50 parts of hydrophilic additive, and then 30 parts of the second auxiliary cross-linking agent pentaerythritol tetraacrylate are added to obtain a pre-water-absorbing layer film with a viscosity of 1500mPa.s. The pre-water-absorbing layer film is applied to the surface of the water-blocking layer film by scraping, and the pre-water-absorbing layer film is cured by EB electron beam irradiation (irradiation voltage of 0.2eMv irradiation penetration depth, irradiation dose of 40kG) to obtain a water-absorbing layer film; wherein the hydrophilic additive includes 25 parts of hydroxyethyl methacrylate and 25 parts of 1-vinyl-2-pyrrolidone NVP; S3: According to the weight parts, 98 parts of EVA resin are added to the mixing tank, and then 0.6 parts of the cross-linking agent tert-butyl peroxycarbonate-2-ethylhexanoate TAEC, 0.4 parts of the first auxiliary cross-linking agent TAIC, 0.4 parts of the first auxiliary cross-linking agent ethoxylated trimethylolpropane triacrylate, 0.3 parts of the coupling agent 3-methacryloxypropyl triethoxysilane and 0.1 parts of the light stabilizer 770 are mixed evenly to form a liquid auxiliary agent, and then the liquid auxiliary agent is sprayed on the EVA resin particles, and then the heating jacket is heated at a temperature of 50°C for 4 hours and then allowed to stand, and finally the outlet module temperature is set to 75°C and the film outlet temperature is set to 95°C for casting, and the EVA layer film is extruded; S4: placing an EVA layer film on the surface of the water-absorbing layer film, and compounding through an embossing roller to obtain a three-layer photovoltaic encapsulation film, wherein the thickness ratio of the water-blocking layer film, the water-absorbing layer film and the EVA layer film is 10:2:33.
[0080] [Example 2] - [Example 3] The difference from Example 1 is that the various raw materials and the amounts of raw material addition in Examples 2-3 are different. The specific components of the photovoltaic encapsulation films of Examples 1-3 are shown in Table 1.
[0081] Table 1 Formula of photovoltaic encapsulation film of Examples 1-3
[0082] [Example 4] - [Example 7] The difference from Example 1 is that the hydrophilic auxiliary agent used in Example 4 is a hydrophilic monomer, and the hydrophilic monomer includes 25 parts of dimethylaminoethyl methacrylate and 25 parts of hydroxyethyl methacrylate.
[0083] The difference from Example 1 is that the hydrophilic additive used in Example 5 includes 20 parts of hydroxyethyl methacrylate (number average molecular weight is 2000) and 5 parts of polyvinyl pyrrolidone (number average molecular weight is 10000).
[0084] The difference from Example 1 is that the ion adsorbent used in Example 6 is zirconium phosphate.
[0085] The difference from Example 1 is that the modified antacid used in Example 7 is modified magnesium hydroxide.
[0086] [Comparative Example 1] A specific preparation process of a photovoltaic encapsulation film includes the following steps: According to the weight proportion, 98 parts of EVA resin are added to a mixing tank, and then 0.6 parts of a cross-linking agent, tert-butyl peroxycarbonate-2-ethylhexanoate TAEC, 0.4 parts of a first auxiliary cross-linking agent TAIC, 0.4 parts of a first auxiliary cross-linking agent, ethoxylated trimethylolpropane triacrylate, 0.3 parts of a coupling agent, 3-methacryloxypropyl triethoxysilane, and 0.1 parts of a light stabilizer 770 are mixed evenly to form a liquid auxiliary agent, and then the liquid auxiliary agent is sprayed onto the EVA resin particles, and then a heating jacket is heated and absorbed at a temperature of 50°C for 4 hours and then allowed to stand, and finally the outlet module temperature is set to 75°C and the film outlet temperature is set to 95°C for casting, and 400g of an EVA layer film is obtained by extrusion; [Comparative Example 2] The difference from Example 1 is that there is no water-absorbing layer film in Comparative Example 2.
[0087] [Comparative Example 3] The difference from Example 1 is that the water absorbing layer film of Comparative Example 3 is replaced by an EVA absorption layer; The preparation method of the EVA adsorption layer is as follows: According to the weight proportion, 98 parts of EVA resin were added to the mixing tank, and then 0.6 parts of the cross-linking agent tert-butyl peroxycarbonate-2-ethylhexanoate TAEC, 0.4 parts of the first auxiliary cross-linking agent TAIC, 0.4 parts of the first auxiliary cross-linking agent ethoxylated trimethylolpropane triacrylate, 0.3 parts of the coupling agent 3-methacryloxypropyl triethoxysilane and 0.1 parts of the light stabilizer 770 were mixed evenly to form a liquid auxiliary agent, and then the liquid auxiliary agent was sprayed onto the EVA resin particles, and then the heating jacket was heated and absorbed at a temperature of 50°C for 2 hours, and then 0.2 parts of anti-polarization masterbatch silica masterbatch (masterbatch content 5%, particle size 50nm) was added and mixed for 2 hours and allowed to stand, and finally the outlet module temperature was set to 75°C and the film mouth temperature was set to 95°C for casting, and the EVA adsorption layer was extruded.
[0088] [Comparative Example 4] The difference from Example 1 is that the antacid in the water-blocking layer film of Comparative Example 4 is not modified.
[0089] The photovoltaic encapsulation films provided in Examples 1-7 and Comparative Examples 1-4 of the present application are used to encapsulate the cells, and then the performance of the encapsulated cells is tested: Corrosion test: laminated parts are made according to the glass / film / cell-TOPCon / film / backplane stacking, and the lamination conditions are 145℃ for 15min; the laminated parts are continued to be heated with heat transfer tape at 145℃ for 5min. Cool and place at a temperature of 23℃±2℃ and a relative humidity of 50%±10% for more than 4h; the laminated parts are placed in a PCT box for testing, and the test conditions are: test temperature 121℃, humidity RH100%. Take out after 24h and 48h, and take EL photos.
[0090] Component reliability: Components were made according to the glass / EVA film / TOPCon battery / EVA film / glass lamination conditions, with lamination conditions of 145°C for 15 minutes; after lamination, they were cooled and framed. The components were exposed to 5.5KW / h for pretreatment, and then the PID96 test conditions were carried out: test temperature 85°C, humidity RH85%, negative bias -1500V. After 96 hours, the components were taken out and kept at a constant temperature for 6 hours, and EL photography and power testing were carried out to obtain the open circuit voltage Voc, fill factor FF, and short circuit current density Jsc of the corresponding battery devices. The test results are shown in Table 2.
[0091] Table 2 Performance test results of photovoltaic encapsulation film encapsulation cells of Examples 1-7 and Comparative Examples 1-4
[0092] It can be seen from Table 2 that compared with Example 1-4, the output power attenuation of the battery cell in Example 1-7 is very small, while the output power attenuation of the battery cell in Comparative Example 1-4 is more serious. This shows that the three-layer laminated photovoltaic encapsulation film in the present application can better maintain the long-term stability and efficiency of the battery cell in a hot and humid environment.
[0093] Combination Figure 3~4 It can be seen from Example 1 and Comparative Example 1 that in Comparative Example 1, no modified antacid is added, the battery cell is severely corroded, and it is difficult to maintain stable conductive properties, resulting in a severe attenuation of the battery cell output power.
[0094] Combination Figures 5 to 15 , Examples 1-7 and Comparative Examples 1-4 show that, Figures 5 to 11 It can be clearly seen that after the PID96 test, the cell darkens to a lesser extent, that is, the cell attenuation is smaller, and Figures 12 to 15 It can be clearly seen that the battery cell has darkened to a large extent, that is, the battery cell attenuation is more serious. The single-layer EVA film used in Comparative Example 1 has little effect on reducing PID, so the output function attenuation is more serious. The encapsulation film in Comparative Example 2 does not have a water-absorbing layer film. Although the modified antacid in the water-blocking layer film can improve the acid resistance and partial water-blocking performance, its contribution to reducing PID is limited. The encapsulation film is still greatly affected by water vapor, and there is no ion adsorbent to adsorb the migrating sodium ions, which leads to a large output power attenuation of the battery cell. In Comparative Example 3, no hydrophilic additive was added to the EVA adsorption layer, and an ion adsorbent was directly added. Then, in a humid and hot environment, the migration speed of sodium ions is faster, and under the influence of more water vapor, the ion adsorbent has an unsatisfactory adsorption effect on sodium ions, which will cause the output power of the battery cell to be greatly attenuated; while in Examples 1-7, the hydrophilic additive and the ion adsorbent work together to form a water-absorbing layer film with an island structure. The island component in the water-absorbing layer film is an ion adsorbent, and the sea component is a hydrophilic additive. When Na + When ions migrate to the battery cell under the action of the electric field, the island component is an ion adsorbent that can adsorb Na +ions, improve the anti-PID effect, the hydrophilic additive is highly water-absorbent, reduces the impact of water vapor on the battery cell, and also provides an environment for the ion adsorbent to adsorb ions, effectively reducing the performance degradation of the battery cell. In Comparative Example 4, the antacid has not been modified, has poor dispersion in the EVA resin, is easy to agglomerate, and has a poor anti-acid effect. The antacids in Examples 1-7 are modified with a carbodiimide coupling agent, which can react with moisture immersed in a hot and humid environment to generate urea, reduce water vapor permeation, and easily react with carboxylic acid generated by hydrolysis of the EVA resin to generate stable ureides, while improving the dispersion of the antacid, it also improves the water barrier performance and the anti-PID effect, thereby improving the hydrolysis stability of the photovoltaic encapsulation film.
[0095] The embodiment of the present application may also provide a photovoltaic module (not shown), which includes a battery cell and the photovoltaic encapsulation film as described above, and the photovoltaic encapsulation film is used to encapsulate the battery cell.
[0096] It should be noted that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The orientation words "inside" and "outside" refer to the inside and outside relative to the outline of each component itself. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Therefore, the exemplary term "above..." can include both "above..." and "below..." orientations. The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used here are interpreted accordingly.
[0097] It should also be noted that "one embodiment", "another embodiment", "embodiment", etc. mentioned in this application refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Further, when describing a specific feature, structure or characteristic in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0098] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0099] It should also be noted that the above are only preferred embodiments of the present application, and the patent protection scope of the present application is not limited thereto. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A photovoltaic encapsulation film, characterized in that: It includes a water-blocking layer film, a water-absorbing layer film and an EVA layer film which are stacked in sequence; The water-blocking layer film comprises the following raw materials in parts by weight: 90-100 parts of EVA resin, 0.4-0.8 parts of cross-linking agent, 0.6-1.0 parts of first auxiliary cross-linking agent, 0.1-0.5 parts of coupling agent, 0.01-0.15 parts of light stabilizer and 0.1-0.3 parts of modified antacid; The water-absorbing layer film comprises the following raw materials in parts by weight: 5-20 parts of ion adsorbent, 25-50 parts of hydrophilic additive, and 30-40 parts of second auxiliary cross-linking agent; The EVA layer film comprises the following raw materials in parts by weight: 90-100 parts of EVA resin, 0.4-0.8 parts of cross-linking agent, 0.6-1.0 parts of first auxiliary cross-linking agent, 0.1-0.5 parts of coupling agent and 0.01-0.15 parts of light stabilizer.
2. The photovoltaic encapsulation film according to claim 1, characterized in that: The hydrophilic auxiliary agent includes one of a hydrophilic monomer and a hydrophilic polymer.
3. The photovoltaic encapsulation film according to claim 2, characterized in that: The hydrophilic monomer includes one or more of hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone NVP, dimethylaminoethyl methacrylate, and polyvinyl pyrrolidone.
4. The photovoltaic encapsulation film according to claim 2, characterized in that: The hydrophilic additive includes a hydrophilic polymer obtained by polymerization of one or more of hydroxyethyl methacrylate, 1-vinyl-2-pyrrolidone NVP, dimethylaminoethyl methacrylate, and polyvinyl pyrrolidone; The number average molecular weight of the hydrophilic polymer is 2000-10000.
5. The photovoltaic encapsulation film according to claim 1, characterized in that: The modified antacid includes one or both of modified magnesium hydroxide and modified magnesium oxide; Wherein, the modified magnesium hydroxide is magnesium hydroxide modified by a carbodiimide coupling agent; and the modified magnesium oxide is magnesium oxide modified by a carbodiimide coupling agent.
6. The photovoltaic encapsulation film according to claim 5, characterized in that: The carbodiimide coupling agent is obtained by using an isocyanate coupling agent under the catalytic action of an organic phosphorus catalyst.
7. The photovoltaic encapsulation film according to claim 1, characterized in that: The ion adsorbent includes one or both of silicon dioxide and zirconium phosphate.
8. The photovoltaic encapsulation film according to claim 1, characterized in that: The crosslinking agent includes one or both of tert-butyl peroxycarbonate-2-ethylhexanoate TAEC and tert-butyl peroxy-2-ethylhexyl carbonate TBEC.
9. The photovoltaic encapsulation film according to claim 1, characterized in that: The first auxiliary cross-linking agent includes one or more of TAIC, tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate and pentaerythritol tetraacrylate.
10. The photovoltaic encapsulation film according to claim 1, characterized in that: The coupling agent includes one or more of 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane.
11. The photovoltaic encapsulation film according to claim 1, characterized in that: The second auxiliary crosslinking agent includes one or more of ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate, tripropylene glycol diacrylate, propoxylated glycerol triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate and pentaerythritol tetraacrylate.
12. A method for preparing a photovoltaic encapsulation film, characterized in that: The steps include: According to the weight percentage, 90-100 parts of EVA resin are added to the mixing tank, and then 0.4-0.8 parts of the cross-linking agent, 0.6-1.0 parts of the first auxiliary cross-linking agent, 0.1-0.5 parts of the coupling agent, and 0.01-0.15 parts of the light stabilizer are mixed and added to the mixing tank, and then heated and heat-insulated, and then 0.1-0.3 parts of the modified antacid are added, and the mixture is allowed to stand and then extruded to obtain a water-blocking layer film; According to the weight ratio, 25-50 parts of the hydrophilic auxiliary agent and 30-40 parts of the second auxiliary cross-linking agent are mixed evenly to obtain a mixed solution, and then 5-20 parts of the ion adsorbent are added to the mixed solution and stirred, and the viscosity is adjusted to obtain a pre-water-absorbing layer film, and then the pre-water-absorbing layer film is roll-coated on the surface of the water-blocking layer film, and after curing treatment, a water-absorbing layer film is obtained; According to the weight percentage, 90-100 parts of EVA resin are added to a mixing tank, and then 0.4-0.8 parts of a cross-linking agent, 0.6-1.0 parts of a first auxiliary cross-linking agent, 0.1-0.5 parts of a coupling agent, and 0.01-0.15 parts of a light stabilizer are mixed and evenly added to the mixing tank, and then heated and heat-insulated and then extruded to obtain an EVA layer film; The EVA layer film is placed on the surface of the water-absorbing layer film, and the photovoltaic encapsulation film is obtained by compounding with an embossing roller.
13. The method for preparing a photovoltaic encapsulation film according to claim 12, characterized in that: The curing treatment includes one of EB irradiation, UV curing or thermal curing.
14. A photovoltaic module, characterized in that: include: Battery cells; The photovoltaic encapsulation film according to any one of claims 1 to 11, or the photovoltaic encapsulation film prepared by the method for preparing the photovoltaic encapsulation film according to claim 12 or 13; The photovoltaic encapsulation film is used to encapsulate the solar cell.
Citation Information
Patent Citations
Bio-based polycarbodiimide cross-linking agent with temperature-sensitive characteristic and preparation method thereof
CN111393595A
Low-temperature laminated thermoplastic high-water-resistance packaging adhesive film and preparation method thereof
CN117165194A
Hydrolysis-resistant modified TPU hot melt adhesive and preparation method thereof
CN117304861A
Composite diaphragm as well as preparation method and application thereof
CN118374835A
Packaging adhesive film and preparation method and application thereof
CN118599438A